AN ASSESSMENT OF THE PENAEID PRAWN SEED RESOURCE OF THE GODAVARI ESTUARY AND THE ADJACENT BACKWATERS - Rao, G Sudhakara (Indian Journal of Fisheries, 2011)
In recent years there has been a growing interest in prawn culture in brackishwaters. Andhra Pradesh, endowed with vast areas of backwaters and estuarine mud flats, offers an ideal environment to develop prawn culture on a commercial scale. The most important input for any sort of farming is the availability of seed near the proposed prawn farms. Though significant breakthrough has been achieved in the spawning and rearing of pcnaeid prawns in hatcheries by the Central Marine Fisheries Research Institute and other agencies, large scale production of prawn seed for commercial purposes is yet to be achieved.